Market prices and demand for essential drugs in Ate district during the COVID-19 pandemic - Saenz Herrera, José Ángel (2022)
Objective: To understand the relation between market prices and the variation in the quantity demanded of essential medicines during the COVID-19 pandemic in the district of Ate. Method: A quantitative approach was used, with a descriptive scope and non-experimental design. In order to gather the perception of pharmaceutical chemists in the district of Ate regarding the behavior of prices and the quantity demanded of medicines, 73 pharmaceutical chemists directly related to the issues were surveyed, and statistical tables were presented to them for analysis and interpretation. Results: Market prices show a remarkable volatility generated by consumer demand for medicines in the district of Ate. Conclusion: Market prices played a significant role in the quantity demanded for medicines, specifically as an effect of their monetary value, free market, and consumer behavior.